Digital Dilemma, Cyber Frauds and Mobile Banking in India (Trinity Journal of Management, IT & Media (TJMITM), 2017)
the contrary, e-security of funds with the help of passwords, PIN,  TIN, OTP, firewall system, traces and detection of unauthorized  transaction are other important aspects of digital banking under  regulatory provisions. Some other forms of electronic  transactions are also popular in India that are not included in legal  Bankers, intermediaries and investors are adapting quality  banking practices and opting for latest advancements in banking  technology for offering better banking solutions. Digital banking is  one of the paramount booms in the last 15 years for the Indian  economy. Indian banking sector is undergoing plethora of  reforms including legal, financial, technological and economic  reforms. With the advent of World Wide Web, Web 3.0, fifth  generation devices, legal framework for dealing with technology,  electronic governance, vigilance and constant innovation in the  field of information technology our lives have become so  complicated as never before. Nevertheless, it has also helped to  bring electronic insurgency in the global banking and financial  transactions. Where banking transactions are carries out in a  speedy, smooth, transparent, paperless, authentic and reliable  manner. Digital banking is a wider term covering all the technical  terminology and ICT tools i.e., e-banking, internet banking, m banking, SMS banking, app banking etc. Moreover, our heavy  dependency on electronic gadgets, mobiles and digital tools to  electronic commence business and routine transactions is also  increasing day by day. Unfortunately, at the same time we are  exposed to many closed and open networks where the reliability  and safety is a challenge for regulatory authority. The growing  trends of cyber frauds including off line and online financial  activities are affecting a large number of population. Financial  frauds with online payments, Mobile banking, ATM machines,  Mobiles data, Electronic cards and net banking transactions are  some challenges faced by banking concerns and IT Experts  where IT department is not core area for banking concern. Most  of the IT operations are outsourced including the security, plastic  money, website maintenance, printing of debit/credit cards,  collection etc. Lupus and other security developers are worried  about security system, virus attacks, app safety for androids and  vault safety.
Keywords: Digital reforms; economic pressure; competition; legal